2001
DOI: 10.1524/zpch.2001.215.7.867
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectral Properties of Substituted Arylazothiobarbiturate Compounds in the Presence of Different Solvents

Abstract: The electronic absorption spectra of 5-(substituted phenylazo) thiobarbituric acid compounds in the presence of different solvents are analyzed by the multiple regression technique using the equation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Various reports had appeared recently discussing the electronic spectral properties of pyrimidine bases and their derivatives [12][13][14][15][16][17][18][19][20][21][22][23]. Pyrimidine is an active component of antibiotics and antineoplastics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports had appeared recently discussing the electronic spectral properties of pyrimidine bases and their derivatives [12][13][14][15][16][17][18][19][20][21][22][23]. Pyrimidine is an active component of antibiotics and antineoplastics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, certain pyrimidine-pyrazoles have been studied in the fight against cancer [9][10][11][12][13][14][15][16][17]. In our laboratory, Masoud et al recently reported a detailed structural chemistry of azo and nitroso metal complexes [18][19][20][21][22][23][24][25][26] based on spectral and magnetic susceptibility measurements. The following paper aimed to study the stability of biologically active nitroso and nitroso-azo compounds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Attention in our laboratory has escalated regarding the potential of those compounds and their complexes owing to their applicability as potential ligands for a large number of metal ions [2][3][4][5][6][7][8][9][10][11][12][13]. Compounds containing nitrogen and sulphur as donor atoms such as thiouracil (TU) and 6-amino-2-thiouracil (ATU) have an important role to play as anti-cancer and anti-viral activities [14].…”
Section: Introductionmentioning
confidence: 99%